Integrating environment and economy : strategies for local and regional government - Roberts, Peter; Gouldson, Andrew (London : Routledge, 2000)
Includes bibliographical references and index
Keywords: Economic development -- Environmental aspects; Environmental economics; Environmental policy -- Economic aspects